Pelatihan Pembuatan Produk Olahan Selai Buah Naga Sebagai Upaya Peningkatan Jiwa Kewirausahaan Pada Siswa SMA Muhammadiyah 2 Genteng Banyuwangi - Setiawan, Andika Putra; Muliasari, Risa Martha; Nalawati, Ara Nugrahayu; Wardhana, Danu Indra; Mananda, Afan Bagus; Prasetyo, Lucky Wahyu; Nuriyatul, Mega Saniya Juli (Kadiri University, 2024)
The harvest season is the moment that farmers have been waiting for because they will get the results of their hard work over the past few months depending on what commodities are planted in the hope of getting maximum yields and high selling prices. The harvest produced by farmers in Banyuwangi Regency is quite abundant, especially dragon fruit, based on data from the Central Statistics Agency (BPS) in 2022, it was recorded at 272,324.7 tons. The superior potential in the agricultural sector makes Banyuwangi Regency a supplier of food, especially dragon fruit. This cannot be separated from the intervention of the younger generation to work, especially in the field of post-harvest processing, so that farmers do not only sell raw goods. Through the Community Service (PKM) partnership program for SMA Muhammadiyah 2 Genteng Banyuwangi students, it aims to improve students' abilities in exploiting opportunities for potential agricultural products, especially dragon fruit which will later be processed into fruit jam. It is hoped that this training will be able to grow the spirit of SMA Muhammadiyah 2 students. Banyuwangi roof tiles. From this training, students will be equipped to develop the agricultural potential in Banyuwangi Regency. This activity was carried out in the form of direct socialization and practice of making dragon fruit jam products, which was attended by 47 students. The results of observing this activity were that students at SMA Muhammadiyah 2 Genteng Banyuwangi had never implemented the practice of making dragon fruit jam. This is based on the results of the pre-test, only 17% of students understand about making fruit jam products, after carrying out the training the level of understanding increased to 93% as evidenced by the results of the post-test. It is hoped that this training in making fruit jam products can foster an entrepreneurial spirit, creativity and innovation in students. Buah naga merupakan salah satu komoditas pertanian unggulan di Kabupaten Banyuwangi. Berdasarkan data Badan Pusat Statistik (BPS) tahun 2022 hasil panen buah naga di Kabupaten Banyuwangi mencapai 272.324,7 ton sehingga menjadi salah daerah satu pemasok buah naga. Hasil panen buah naga yang melimpah menjadikan prospek olahan produk pasca panen menjanjikan karena bahan baku mudah didapatkan. Melalui program kemitraan Pengabdian Kepada Masyarakat (PKM) Pada Siswa SMA Muhammadiyah 2 Genteng Banyuwangi bertujuan untuk meningkatkan kemampuan siswa dalam pemanfaatan peluang akan potensi hasil pertanian kususnya buah naga yang bisa diolah menjadi produk selai buah, diharapkan adanya pelatihan ini mampu menumbuhkan jiwa kewirausahaan terhadap siswa SMA Muhammadiyah 2 Genteng Banyuwangi. Sehingga dari pelatihan tersebut akan menjadi bekal peserta didik untuk mengembangkan potensi pertanian yang ada di Kabupaten Banyuwangi. Kegiatan ini dilaksanakan berupa sosialisasi dan praktek pembuatan produk selai buah naga secara langsung yang diikui oleh 47 siswa. Hasil dari observasi kegiatan tersebut siswa SMA Muhammadiyah 2 Genteng Banyuwangi belum pernah melaksanakan praktek pembuatan selai buah naga. Hal ini dilandasi dari hasil pre-test hanya 17% siswa yang memahami tentang pembuatan produk selai buah, setelah melaksanakan pelatihan tingkat pemahaman meningkat menjadi 83% dibuktikan dari hasil pos-test. Pelatihan pembuatan produk olahan selai buah ini diharapkan dapat menumbuhkan jiwa entrepreneur, kreativitas, dan inovasi pada siswa.